2009
DOI: 10.1371/journal.pone.0006397
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Virus at the Evolutionary Intersection of Three Types of Large DNA Viruses; Iridoviruses, Ascoviruses, and Ichnoviruses

Abstract: BackgroundThe ascovirus, DpAV4a (family Ascoviridae), is a symbiotic virus that markedly increases the fitness of its vector, the parasitic ichneumonid wasp, Diadromus puchellus, by increasing survival of wasp eggs and larvae in their lepidopteran host, Acrolepiopsis assectella. Previous phylogenetic studies have indicated that DpAV4a is related to the pathogenic ascoviruses, such as the Spodoptera frugiperda ascovirus 1a (SfAV1a) and the lepidopteran iridovirus (family Iridoviridae), Chilo iridescent virus (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…DNA sequence analysis showed that HvAV-3g has a genome size of 199,721 bp, which is the largest among all the reported ascovirus genomes to date (2,3,5,14). The HvAV-3g genome has a GϩC content of 45.9%, which is similar to that of HvAV-3e (45.8%) but dissimilar to that of SfAV-1a (49.2%), TnAV-2c (35.4%) and DpAV-4a (49.66%) (2,3,5,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequence analysis showed that HvAV-3g has a genome size of 199,721 bp, which is the largest among all the reported ascovirus genomes to date (2,3,5,14). The HvAV-3g genome has a GϩC content of 45.9%, which is similar to that of HvAV-3e (45.8%) but dissimilar to that of SfAV-1a (49.2%), TnAV-2c (35.4%) and DpAV-4a (49.66%) (2,3,5,14).…”
mentioning
confidence: 99%
“…The HvAV-3g genome has a GϩC content of 45.9%, which is similar to that of HvAV-3e (45.8%) but dissimilar to that of SfAV-1a (49.2%), TnAV-2c (35.4%) and DpAV-4a (49.66%) (2,3,5,14). There are 194 open reading frames (ORFs) encoding predicted proteins of more than 50 amino acids.…”
mentioning
confidence: 99%
“…Ascoviruses (AVs) are pathogenic to lepidopteran insects at larval and pupal stages (6). After infection, the host cell morphology resembles that of apoptotic cells producing vesicles that look like apoptotic bodies through which virions are disseminated (5).…”
mentioning
confidence: 99%
“…The virions can be transmitted mechanically by the ovipositor of female parasitic wasps between caterpillars (15). Genome sequences (119-to 187-kbp dsDNA) of four recognized AV species, Spodoptera frugiperda AV (SfAV-1), Trichoplusia ni AV (TnAV-2), Heliothis virescens AV (HvAV-3), and Diadromus pulchellus AV (DpAV-4) are now available (1,4,6,30). Phylogenetic studies suggest that AVs may have evolved from iridoviruses that infect lepidopteran larvae (15,29).…”
mentioning
confidence: 99%
“…These viruses possess a single circular double-stranded DNA genome ranging from 119 to 186 kbp and is encapsidated in virions of allantoid to bacilliform shapes (10). There are four recognized AV species, Spodoptera frugiperda AV (SfAV-1), Trichoplusia ni AV (TnAV-2), Heliothis virescens AV (HvAV-3), and Diadromus pulchellus AV (DpAV-4), and their complete genome sequences now are available (1)(2)(3)31). AVs are transmitted by wasp vectors, and their association with the vector could either be antagonistic (SfAV-1, TnAV-2, and HvAV-3) or mutualistic (DpAV-4) (4).…”
mentioning
confidence: 99%